2018
DOI: 10.1299/mej.17-00444
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of high-frequency dynamic properties of squeezed O-ring for bearing support

Abstract: Determination and prediction of the dynamic properties of an O-ring for bearing support were performed. Utilizing O-rings as supporters of bearing is a promising way to suppress severe vibrations such as resonance and self-excited whirl experienced in high-speed turbo machinery. However, analytical prediction of the dynamic properties of O-rings has not been very successful so far because of its non-linear dependence on many parameters. In this study, focusing on the incompressibility of rubber materials, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They also concluded that both stiffness and damping coefficients increase when the ring thickness increases. [ 78 ] calculated using FEM and verified experimentally the dynamic coefficients of squeezed O-rings used to support high-speed bearings of high-speed turbo machinery. The concluded that the stiffness coefficient of the O-rings increases with frequency [ 12 ].…”
Section: The Effect Of the Elastic Rings Geometrical Parameters On Th...mentioning
confidence: 96%
“…They also concluded that both stiffness and damping coefficients increase when the ring thickness increases. [ 78 ] calculated using FEM and verified experimentally the dynamic coefficients of squeezed O-rings used to support high-speed bearings of high-speed turbo machinery. The concluded that the stiffness coefficient of the O-rings increases with frequency [ 12 ].…”
Section: The Effect Of the Elastic Rings Geometrical Parameters On Th...mentioning
confidence: 96%
“…A model using 1D beam elements as well as a 3D model using tetrahedral elements has been set up to determine the radial and tilting stiffness k r and k t . O-Rings, whose dynamic characteristics are highly dependent on the excitation frequency [11,18,19,20,21], the membrane measurement results suggest that the radial stiffness k r is independent of the excitation frequency f , which makes their use as a flexible support for HGJB bushings significantly easier and more predictable.…”
Section: Model Verificationmentioning
confidence: 99%
“…While breakaway transients occur as a transition from sticking or pre-sliding to the sliding state due to the release of pre-stress between the contact opponents, dynamic friction behavior occurs while relative motion or sliding takes place at the macro-scale. When friction reduction in elastomer-metal coupled contacts is induced by ultrasonic vibrations, these two friction states are accompanied, besides material wear, with multi-frequency excited friction characteristics, such as variations of contact stiffness, variations of shear stress distribution [13] and local occurrences of glass transitions [14,15]. Thus, the experimental investigation of ultrasonic friction reduction requires individual identifications of these effects.…”
Section: Introductionmentioning
confidence: 99%